The Effectiveness of Physical Education Learning in Elementary School Located in Wetland Environment - Mashud Mashud (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This paper aims at finding out the effectiveness of Physical education subject in elementary school in wetland areas. This paper used qualitative and quantitative descriptive research. This paper took the entire schools in wetland areas (around Banjar and Baritokuala Regency) as the population. The sample of this research was taken by using a purposive sampling method. This paper used the assessment instrument of the teacher’s ability, which focuses on the learning stage (Pre-, during, and Post-) and interview guidelines. The data obtained were analyzed using quantitative and qualitative descriptive analysis. The results found that the Physical education subject of elementary school is ineffective. This paper found several points as contributing factors, they are: (1) environmental factors, (2) school management factor, (3) teacher factors, and (4) customary factors.Abstrak: Makalah ini bertujuan untuk mengetahui efektivitas mata pelajaran pendidikan jasmani di sekolah dasar di daerah lahan basah. Makalah ini menggunakan penelitian deskriptif kualitatif dan kuantitatif. Populasi penelitian ini adalah seluruh sekolah di daerah lahan basah (sekitar Banjar dan Kabupaten Baritokuala). Sampel penelitian ini diambil dengan menggunakan metode purposive sampling. Penelitian ini menggunakan instrumen penilaian kemampuan guru, yang berfokus pada tahap pembelajaran (Pra-, selama, dan pasca-) dan pedoman wawancara. Data yang diperoleh dianalisis menggunakan analisis deskriptif kuantitatif dan kualitatif. Hasil penelitian menemukan bahwa mata pelajaran pendidikan jasmani sekolah dasar tidak efektif. Penelitian ini menemukan beberapa poin sebagai faktor yang berkontribusi, yaitu (1) faktor lingkungan, (2) faktor manajemen sekolah, (3) faktor guru, dan (4) faktor adat istiadat.